Dimensi Sosial Disabilitas Mental di Komunitas Semin, Yogyakarta. Sebuah Pendekatan Representasi Sosial - Petra W. B. Prakosa (Faculty of Psychology, Universitas Gadjah Mada, 2005)
The aim of this study is to analyze the social dimension of mental disability in Semin Yogyakarta. Representational Theory as the basic thinking of qualitative approach in this research, is used to explore the public attitude about mental disability. 20 subjects who participated were derived from 3 different groups in the society. They are 1) the professionals, 2) normal people 3) person with mental disability. The result shows that the people’s social representation about mental disability create attitude which implies social interaction’s unbalancing. Each group which comes from different social segment give different representation and meaning about abnormality. It becomes an individual reference to act differently in their community. This can influence the implementation of social disability program run by professionals, and also creates a social reality for the person with mental disability and his family. The conclusion is, the understanding about social representational dynamic can be the strategy in recognizing back the psychological needs of community related to mental disability problems. Keywords: representational theory, mental disability